Lesena gradnja in požari srednjeveških mest - Kušar, Domen (Les (Ljubljana), 2001)
Timber was one of the key material which contributed to the formation and development of Medieval towns. Primarily, timber was used as the major material for construction of dwellings as there was a large amount of timber around and the demand rather low. Due to expansion of the towns and the increased demand for timber in other areas the 15th century signalled the beginning of the reduction in the availability of timber. At the same time as timber is a combustible material this helped for the Medieval towns to burn to the ground. Therefore, the townspeople wanted to replace it with a safer material which was, particulary at the beginning, rather expensive. The lack of timber caused its price to rise. Thus, timber started to be replaced by other fireproof materials which were demanded and in various ways encouraged by the town authorities. Thus more and more the myth of the timber unsuitibleness for building were put into the force, which, however, is not true. The timber that was retained in buildings was there where it was found to be indispensable due to its properties.
Keywords: les; srednjeveška mesta; gradnja; požari